A single-cell RNA sequencing atlas of the healthy canine lung: a foundation for comparative studies - Rizzoli, Elodie; Fievez, Laurence; Fastrès, Aline; Roels, Elodie; Marichal, Thomas; Clercx, Cécile (Frontiers in Immunology, 2025)
Single cell RNA sequencing (scRNA-seq) can be used to resolve the cellular and molecular heterogeneity within a tissue by identifying cell populations with an unprecedented granularity along with their transcriptional signatures. Yet, the single cell gene expression profiles of cell populations in the healthy canine lung tissue remain unexplored and such analysis could reveal novel cell populations or markers lacking in dogs and facilitate comparisons with lung diseases. Using fresh healthy lung biopsies from four dogs, we conducted droplet-based scRNA-seq on 26,278 cells. We characterized 46 transcriptionally distinct cell subpopulations across all lung tissue compartments including 23 immune, 13 mesenchymal, five epithelial and five endothelial cell subpopulations. Of note, we captured rare cells such as unconventional T cells or Schwann cells. Differential gene expression profiles identified specific markers across all cell subpopulations. Fibroblasts clusters exhibited a marked transcriptional heterogeneity, some of which might exert immune regulatory functions. Finally, the integration of canine lung cells with an annotated human lung atlas highlighted many similarities in gene expression profiles between species. This study thus provides an extensive molecular cell atlas of the healthy canine lung, expanding our knowledge of lung cell diversity in dogs, and providing the molecular foundation for investigating lung cell identities and functions in canine lung diseases. Besides, the occurrence of spontaneous lung diseases in pet dogs, with phenotypes closely resembling those in humans, may provide a relevant model for advancing research into human lung diseases.